Pengaruh Media Pembelajaran Berbasis AI Terhadap Perkembangan Kognitif Siswa Sekolah Dasar - Nefa Rohmadina; Ega Wiwik Urbaningrum; Aneyla Camaliya Audrey Afandie; Bunga Ericia Putri Rifanda; Nuria Elsa Aulia (Prosiding Konferensi Ilmiah Dasar, 2026)
This research intends to investigate the use of artificial intelligence (AI) as a learning medium to enhance the cognitive development of elementary school children. The method employed in this research is a simple literature review that examines several relevant scientific articles on the use of AI in elementary school instruction. The study results demonstrate that AI-based media like interactive multimedia, educational chatbots, adaptive learning systems, digital simulations, and digital comics contribute to the enhancement of students’ conceptual understanding, analytical skills, logical reasoning, working memory, problem-solving, and critical thinking. However, the efficacy of the AI is not dictated just by the sophistication of the technology but also by the compatibility of the media design to the child's cognitive development stage, teacher preparedness, and learning environment support. These results suggest that AI is better viewed as a supportive learning medium that gradually aids the learning process rather than replacing the teacher's function the learning process rather than replacing the function of the teacher. The application of AI in primary schools must be pedagogically, culturally, and adaptively structured to maximally promote the cognitive development of pupils.